2016
DOI: 10.3748/wjg.v22.i27.6095
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genotypes in Myanmar

Abstract: Myanmar is adjacent to India, Bangladesh, Thailand, Laos and China. In Myanmar, the prevalence of hepatitis C virus (HCV) infection is 2%, and HCV infection accounts for 25% of hepatocellular carcinoma. In this study, we reviewed the prevalence of HCV genotypes in Myanmar. HCV genotypes 1, 3 and 6 were observed in volunteer blood donors in and around the Myanmar city of Yangon. Although there are several reports of HCV genotype 6 and its variants in Myanmar, the distribution of the HCV genotypes has not been w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In particular, Myanmar is a resource‐constrained country with approximately 1‐2% of its population chronically infected with HCV . Genotypes 3 (33%‐80%), 6 (16%‐60%) and 1 (9%‐25%) account for the majority of HCV infection, with varying frequencies across different regions . Thus, the heterogeneity in genotype adds to the complexity of treating HCV in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Myanmar is a resource‐constrained country with approximately 1‐2% of its population chronically infected with HCV . Genotypes 3 (33%‐80%), 6 (16%‐60%) and 1 (9%‐25%) account for the majority of HCV infection, with varying frequencies across different regions . Thus, the heterogeneity in genotype adds to the complexity of treating HCV in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Genotypes 3 (33%-80%), 6 (16%-60%) and 1 (9%-25%) account for the majority of HCV infection, with varying frequencies across different regions. 7 Thus, the heterogeneity in genotype adds to the complexity of treating HCV in Myanmar. Genotype 3 HCV infection is particularly concerning because it directly interacts with lipid metabolism and increases cellular triglyceride accumulation; patients commonly exhibit increased levels of steatosis, fibrosis and higher HCC incidence as well as a lower SVR rates.…”
mentioning
confidence: 99%
“…The subtype 6n was prevalent in China, Myanmar and other Southeast Asian countries (e.g., Thailand, Malaysia), while the subtype 6a was mainly circulating among IDUs in the south part of China, including Yunnan (Zhang et al, 2011, 2013; Chen et al, 2015; Qi et al, 2016; Wan et al, 2016), and the subtype 6m was mainly found in blood donors of Myanmar and Thailand (Shinji et al, 2004; Jutavijittum et al, 2009; Wasitthankasem et al, 2015). Interestingly, the prevalence of subtypes 6xa and 6xg were restricted to the China–Myanmar border region (Lwin et al, 2007; Zhang et al, 2013; Chen et al, 2015; Win et al, 2016). As a newly identified subtype, 6xg accounted for 12.0% (3/25) of all strains sampled in Kachin, and 6.0% (15/249) in Dehong prefecture, indicating that 6xg has become the main genotype 6 strains circulating in the China–Myanmar border region after the subtypes 6n and 6xa (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, sample size of the studies is relatively small, in which additional epidemiology studies would have offered more accurate conclusions . Other endemic countries for GT6 are Vietnam, Thailand and Myanmar, although the most prevalent genotypes in Thailand, Myanmar and Vietnam are 3a, 3b and 1a, respectively . Interestingly, a recent study from Thailand reported the decline in prevalence of HCV by half in the past decades but opposed to other genotypes, GT6 turned out to have an increasing trend (9%‐34%) .…”
Section: Epidemiologymentioning
confidence: 97%